THE EVOLUTION AND IMPACT OF COLLABORATIVE LEADERSHIP ACROSS SECTORS: A SYSTEMATIC REVIEW OF RECENT EVIDENCE (2019-2024) - Raharjo, Tri Puji; Purnomo, Indriyanto Dian; Tlonaen, Alex Willem; Taurensa, Vera; Petrahaurissa, Hendra Yuda; Indrianto, Agus; Wahyudi, Ifan; Kurniawan, Harry (Ikatan Dosen Menulis, 2024)
This systematic review examines the evolution and impact of collaborative leadership across organizational sectors from 2019 to 2024. Through analysis of 145 peer-reviewed articles from the Scopus database, the study investigates emerging patterns, implementation challenges, and outcomes of collaborative leadership practices. The review employed the PRISMA methodology, incorporating both qualitative thematic analysis and quantitative synthesis. Findings reveal significant growth in empirical research post-pandemic, with notable advances in healthcare (31%), education (27%), public administration (22%), and business sectors (20%). Organizations implementing collaborative leadership demonstrated improved performance metrics, with healthcare showing the highest improvement rates (78%) and educational institutions achieving strongest stakeholder engagement (85%). Three key trends emerged: increasing integration of digital technologies, growing emphasis on cross-sectoral applications, and evolution toward adaptive leadership models. Success factors include clear governance structures, investment in digital collaboration tools, and continuous leadership development, while primary challenges involve resistance to change (65%) and communication barriers (58%).